Posisi Hadis dalam Ijtihad Muhammadiyah - Mukhlis Rahmanto (Afkaruna: Indonesian Interdisciplinary Journal of Islamic Studies, 2014)
This article examines the dynamics of Muslim understanding of Hadith (Islamic tradition) by exploring the views of Islamic associations in Indonesia. It addresses questions such as a) how is hadith understood by a limited number of ulama (Islamic scholars) and in turn their understanding of hadith become a determinant factor in shaping organizational ideology; b) what is the consequence of the status of a hadith determined by ulama to the dynamics of a collective ijtihad within the organization. The author uses historical and sociological approach in understanding Indonesian Muslim views by paying attention particularly to the Muhammadiyah. This article concludes that the status of a hadith in the Muhammadiyah is determined through collective ijtihad (jama’i); b) the process of authentication and verification of hadith collectively has had a profound impact on the dynamics of Muslim discourse among the members of the Muhammadiyah, and as a result, a structural approach by the members of the Muhammadiyah has sidelined the dynamics of Muslim discourse in the grassroots level. Keywords: Hadith, Muhammadiyah, Ulama (Islamic Scholars), ijtihad,